Bridging Policy and Practice: ICT Tools and Instructor Support in Adult Education Centers in Coastal Tanzania - Binuru Kivaria; Prospery Mwansa Mwila (Journal of Education and Teacher Training Innovation, 2025)
The integration of Information and Communication Technology (ICT) in adult education is widely recognized as a critical driver of inclusive learning, instructional effectiveness, and lifelong skills development. Despite supportive national policies in Tanzania, evidence suggests that the translation of these policy intentions into practice within adult education centers remains uneven. This study examined the availability of ICT tools and the nature of instructor support services in adult education centers in the Coastal Region of Tanzania, with the aim of understanding how policy commitments are reflected at the implementation level. A mixed-methods approach within a cross-sectional research design was employed. Quantitative data were collected through structured questionnaires administered to 40 adult learners and 16 instructors, while qualitative data were obtained through semi-structured interviews with 4 adult education center coordinators and direct observations using checklists. Descriptive statistical analysis was conducted using IBM SPSS, while qualitative data were analyzed thematically. The findings indicate that while basic infrastructure such as electricity and limited internet connectivity is generally available, critical ICT tools including computers, projectors, and printing equipment are insufficient and unevenly distributed across centers. Both instructors and learners demonstrated positive perceptions of the usefulness of ICT in teaching and learning; however, actual integration of ICT into instructional practices was irregular. Instructor support services, particularly training, mentoring, and technical assistance, were found to be inconsistent and largely inadequate. These gaps contribute to a disconnect between ICT policy aspirations and classroom realities. The study underscores the need for targeted investment in ICT infrastructure, sustained professional development for instructors, and strengthened institutional support mechanisms to enhance effective ICT integration in adult education settings